1987
DOI: 10.1007/bf03015328
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cremophor EL in the anaesthetized dog

Abstract: The effects of cremophor EL in the anaesthetized dogThe effects of cremophor EL were studied in 13 in PCWP, per cent at the end of infusion, -32 per cent 150 minutes after the end of infusion). Heart rate and systemic vascular resistance did not vary significantly. Pulmonary vascular resistance increased at the end of infusion, five and ten minutes after the end of infusion (+ 734, +548 and +439 per cent respectively). Plasma volume decreased I0 and 30 minutes after the end of infusion (-28 and -30.5 per ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The marmoset can be used for pharmacology as well as for toxicology studies. In addition, there are well-established classes of compounds where the marmoset may well offer an alternative species to the dog that shows hypersensitivity or idiosyncrasy (Smith et al, 2001;Gaudy et al, 1987) (Table 6).…”
Section: Toxicologymentioning
confidence: 99%
“…The marmoset can be used for pharmacology as well as for toxicology studies. In addition, there are well-established classes of compounds where the marmoset may well offer an alternative species to the dog that shows hypersensitivity or idiosyncrasy (Smith et al, 2001;Gaudy et al, 1987) (Table 6).…”
Section: Toxicologymentioning
confidence: 99%
“…[23][24][25] Cremophore EL emulsion has fewer lipophilic characteristics and easily crosses membranes and distributes among serum lipoproteins. Drug given with cremophore is also related to a slower clearance from the plasma and the parallel slower uptake in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Thus, rapid absorption and longer residence were observed when using the cremophore formulation with various drugs. [24][25][26][27][28] The formulations of AM or AE with sesame oil (slow absorption) and cremophore (fast absorption) were also compared with their efficacy potency against Plasmodium berghei in mice. In addition, DQHS, an active metabolite of both AE and AM, is known to be extremely toxic in rats; 20 we also included it for comparison with AE and AM in this study.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that Cremophor EL induces hypersensitivity reactions in up to 9% of all human patients despite pretreatment . Hypersensitivity reactions also occur at a high rate in dogs, and the observations are similar to those in humans …”
Section: Introductionmentioning
confidence: 69%